Frontoparietal cavernous malformation in a 39-year-old woman: a case report - Sallem, Camilla Costa; Teixeira, Beatriz Esmeraldo; Sá, Caio Sérgio Gomes; Lima, Lara Maria Fujita Vieira; Barros, Letícia Passos Chaves Capibaribe; Santos, Nayla Lima dos; Andrade, Halisson Rodrigues de; Garcia, Tulia Fernanda Meira; Alencar, Felipe Rios Moraes Andrade de; Rivelli, Álvaro Moreira Rivelli; Santos, Júlio César Claudino dos (Brazilian Journal of Case Reports, 2023)
Cerebral cavernous malformation (CCMs) is an angiographically occult, low-flow neurovascular disease resulting from capillary dilatation of cerebral blood vessels that may also occur in the spinal cord, causing extravasation of blood cells from the affected vessel that leads to multiple repercussions in the patient’s life. This condition’s clinical characteristics include recurrent bleeding, seizures, persistent neurological deficits, epilepsy, and death. In this study, we describe the clinical course of a patient with a Cavernous Malformation and its prognosis regarding the association between clinical progression and therapeutic perspectives. It’s relevant to elucidate possible lack of studies that may urge further research on this theme and new learning pathways should be opted for to increase awareness of this condition in order to improve its prognosis.